Проблеми застосування заохочень у цивільному праві - Чалий, Ю. І.; Chalyi, Yu. I.; Юрій Чалий (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 3 (106). - С. 55-64, 2024)
Зазначено, що заохочення нечасто застосовують у цивільному праві через об’єктивні та суб’єктивні причини. Об’єктивними причинами є особливості самої праворегулятивної методології цивільного права, суб’єктивними – відсутність достатньо розроблених загальних положень у цивілістичній доктрині та брак норм подібного змісту в цивільному законодавстві. Усунення перешкод суб’єктивного характеру в перспективі дозволить інтенсифікувати застосування заохочень при саморегулюванні цивільних відносин.

The article notes that incentives are rarely used in civil law due to both objective and subjective reasons. The objective reason is the peculiarities of the law-regulatory methodology of civil law itself, but they are not an obstacle to the use of incentives in civil law. The specifics of the civil law methodology only determine a certain secondary importance of incentives as legal means of regulating civil relations, but do not exclude the possibility and necessity of their application in general. The subjective reasons are the lack of sufficiently developed general provisions in the civil law doctrine and the lack of provisions of similar content in civil law. Elimination of the latter two subjective obstacles will in the future allow intensifying the use of incentives in the self-regulation of civil relations. Based on the principles of freedom of contract and freedom of unilateral transactions, civil law subjects are free to choose the methods of regulating their relations. This freedom also applies to their choice of incentives as legal means of regulating their individual relations. Increased use of incentives in civil law should be expected primarily in self-regulatory relations. The advantage of using incentives, as compared to the methods of ensuring proper performance of obligations (pledge, surety, retention, etc.), as well as measures of civil liability or other legal consequences, is that incentives are positive sanctions by their nature, i.e. a reward for making maximum efforts to achieve a certain legal result by the subject. This circumstance allows the parties to contractual legal relations to strengthen their ties and create an atmosphere of trust rather than suspicion. This is especially important for contractual relations in the business sector, where the duration of economic and legal relations is one of the determining factors of business success. The use of methods to ensure the proper fulfilment of contractual obligations, and even more so, measures of liability or other legal consequences for breach of obligations, generates negative tension or even leads to the termination of business relations.

Отмечено, что поощрения редко применяют в гражданском праве по объективным и субъективным причинам. Объективными причинами являются особенности самой праворегулятивной методологии гражданского права, субъективными - отсутствие достаточно разработанных общих положений в цивилистической доктрине и нехватка норм подобного содержания в гражданском законодательстве. Устранение препятствий субъективного характера в перспективе позволит интенсифицировать применение поощрений при саморегулировании гражданских отношений.
Problems of applying incentives in civil law
Keywords: заохочення в цивільному праві; заохочувальні норми цивільного права; заохочення як правові засоби регулювання цивільних відносин; стимули в цивільному праві; методологія правового регулювання цивільних відносин; incentives in civil law; civil law incentive provisions; incentives as legal means of regulating civil relations; stimuli in civil law; methodology of legal regulation of civil relations; поощрение в гражданском праве; поощрительные нормы гражданского права; поощрение как правовые средства регулирования гражданских отношений; стимулы в гражданском праве; методология правового регулирования гражданских отношений